Tribological analyses of modified jatropha oil with hBN and graphene nanoparticles as an alternative lubricant for machining process - Jamaluddin, Nor Athira; Talib, Norfazillah; Abdul Sani, Amiril Sahab (Penerbit Akademia Baru, 2020)
The increase of health and environmental consciousness has motivated the effort of technology improvement on lubrication by finding and exploring another potential alternative to replace mineral-based metalworking fluids. Due to this concern, vegetable-based oils have been recognised as an ideal lubricating base oil in machining due to low toxicity, biodegradable, and renewable energy sources. Moreover, nanofluids have attracted enormous attention in the field of lubrication due to excellent physical and chemical properties that can enhance tribological characterisation. The objective of the current work is to develop a new formulation of nanofluids in modified jatropha oil (MJO) by adding hexagonal boron nitride (hBN) and graphene nanoparticle additives at the lowest concentration (0.01, 0.025. and 0.05 wt. %). The physicochemical tests in terms of kinematic viscosity and viscosity index were conducted and compared with synthetic ester (SE). Tribology testing was conducted through four-ball test to determine the coefficient of friction, mean wear scar diameter, and friction torque. The result shows a significant improvement of MJO samples by adding nanoparticle additives compared to the SE. MJOg2 (MJO + 0.025 wt. % of graphene) exhibited excellent tribological behaviour by providing the lowest coefficient of friction and friction torque. Meanwhile, MJOh1 (MJO + 0.01 wt. % of hBN) provided with a smaller mean wear scar diameter among other lubricant samples. Conclusively, the addition of nanoparticle additives significantly enhanced the tribological characteristics and is highly suitable as a substitute for SE.